Computational simulation of the effects of interfacial tension in microfluidic flow focusing droplet generators - Stevens, Matthew; Balaur, Eugeniu; Abbey, Brian (Frontiers in Physics, 2023)
We present simulations of a square flow focusing droplet generator device exploring its performance characteristics over a range of interfacial surface tension values and varying neck width. Droplet generators have a wide range of applications from drug delivery to X-ray diffraction experiments. Matching the droplet frequency and volume to the experimental parameters is critical for maximising the data quality and minimising sample waste. Whilst varying the interfacial surface tension we observed that the lowest frequency of droplets is generated for surface tensions matching those typically reported for water-oil mixtures (around 40 mN/M). Decreasing or increasing the interfacial surface tension, for example by adding surfactant, results in an increase in droplet frequency. We also find that under the conditions simulated here, droplets are generated with much lower capillary numbers and higher Weber numbers than have typically been reported in the literature. The high ratio of flowrate-to-cross-section used here resulted in a velocity which was larger than has previously been reported for flow focusing devices and consequently we observe particularly large associated Reynolds numbers. However, in general, the simulated flow behaviour characteristics most closely match those typically observed for the jetting and tip-streaming regimes. The highest frequency of droplets achieved in our simulated devices was 36 kHz and 56 kHz corresponding to square neck channel widths of 12.5 and 25 µm respectively, an interfacial surface tension of 118.75 mN/m. We also examined the effect of varying neck width geometry for a fixed interfacial surface tension of 52 mN/m. We observed that the highest frequency droplet generation, 61 kHz, corresponded to a neck width of 37.5 µm with a corresponding droplet diameter of 22 µm. The high frequency, high monodispersity, and small droplet size predicted to occur through modification of the interfacial surface tension will have implications for the future design and optimisation of droplet-on-demand microfluidic devices.